Migration Flow and Social Protection Policy: Case Study Indonesia – Malaysia - Wijayanti, Febry; Turgel, Irina Dmitirevna (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2021)
Nowadays, the rest of the world concentrates on increasing global economies through the development of technology and productivity growth. This intent creates uneven economic opportunities, inequality, and social disparity between developed, developing, and undeveloped countries. On the other hand, the discrepancy between them contributes to increasing the migration flow, particularly in ASEAN. Moreover, the population movement between Indonesia-Malaysia majority is a low-skilled migrant and brings several problems for both countries. Thus, the scheme of social protection for a migrant becomes a crucial matter to implement. Hence, this paper aims to acknowledge the migration flow and assess Indonesia and Malaysia's social protection schemes. The result shows that distance is an essential variable of Indonesia's worker migrant than Malaysia's wage rate. Hence, the discourse for stopping worker migrants, particularly domestic workers, is not a great solution. Notably, the government should create a proper MoU with Malaysia to protect worker migrants, particularly domestic workers.